ИННОВАЦИОННЫЕ ПРОЕКТЫ ДЛЯ УСТОЙЧИВОГОРАЗВИТИЯ ЛАНДШАФТА В ЗОНЕ ПУСТЫНЬ (KIUT Publication, 2025)
The modern urban environment of large and major cities is perceived as aggressive from an ecological standpoint. Creating an ecologically favorable living environment is one of the primary objectives of contemporary construction, on par with ensuring the safety of buildings and structures.In this regard, an arcological approach to shaping the architectural and landscape environment can be considered. This approach results in the creation of microclimatic zones and the development of structures with integrated greenery and artificial landscapes.Undoubtedly, this can contribute to improving the qualitative characteristics of the urban environment, as well as enhancing its visual appeal.